Water, Sanitation, and Hygiene Service Ladders and Childhood Diarrhea in Haramaya Demographic and Health Surveillance Site, Eastern Ethiopia - Samuel Wagari; Haileyesus Girma; Abraham Geremew (SAGE Publishing, 2022)
Background: The WHO/UNICEF Joint Monitoring Program (JMP) service ladders are worldwide indicators for monitoring drinking water, sanitation, and hygiene elements of the sustainable development goal targets. However, evidence on how the prevalence of childhood diarrhea looks across the service ladders is limited. This study aimed to assess the relationship between WASH service ladders and the prevalence of childhood diarrhea in Haramaya Demographic and Health Surveillance site, Eastern Ethiopia. Methods: A cross-sectional study using a structured questionnaire, observational checklist, and water quality analysis was conducted on 535 households with children under 5 years of age. Poisson regression with a robust error variance estimator was used to investigate the relationship between dependent and independent variables. Results: The prevalence of diarrhea among under-five children in the surveillance site was 24.8% (95% CI: 22.3-27.6). The regression model revealed that water and sanitation service ladders were associated with childhood diarrhea. Childhood diarrhea was found to be 73% (APR = 0.27; 95% CI: 0.12-0.57) less common in families with a basic water service ladder than in households with a surface water service ladder. In addition, children in households with basic sanitation services had 83% (APR = 0.17; 95% CI: 0.05-0.56) lower diarrhea prevalence than children in households where open defecation was practiced. Conclusion: The present study found that childhood diarrhea differed considerably among WASH service levels and continues to be a serious health problem at the surveillance site. This study also shows that much work is needed to improve WASH services.